Urban Area Policy Innovation From The Perspective of Public Policy in Serang Municipality, Indonesia - Sururi, Ahmad (Jurnal Transformative, 2024)
This article aims to discuss the policy implications and criteria for ideal urban area policy innovation from a public policy perspective. This research was conducted using a case study approach using semi-structured interview data collection techniques as a data collection instrument. The results of the research show that the policy implications for urban residential areas in Serang City are still not optimal due to the limited authority of the city government and the lack of integration of SiKasep policy innovations with urban needs and problems. Apart from that, SiKasep policy innovations have not been able to have an impact due to the low ability and willingness to innovate within the civil service. country. The policy innovation criteria for ideal urban residential areas in Serang City can be applied through the New Public Services (NPS) approach as a representation of policy innovation. Research findings show the importance of strengthening regulations and legitimacy, especially in formulating programs and policies for urban residential areas that are based on regional policy standards; second, the importance of encouraging policy interventions related to access to basic services for the community; third, it is important to encourage policy actors to develop integrated programs and minimize the various interests that hinder policy innovation in urban residential areas; and fourth, participation and involvement of non-governmental elements is very important to obtain broader policy support.